PENGARUH DURASI BERMAIN GADGET TERHADAP KUALITAS TIDUR PADA ANAK USIA SEKOLAH KELAS V DAN VI (SEKOLAH DASAR KRISTEN CITRA BANGSA) - Inka Claudya Setia Budi Chandra; Florentianus Tat; Balbina Antonelda M Wawo (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2022)
Good quality sleep produces physiological and psychological balance at the time of awakening. Students who use gadgets with inappropriate time durations will affect students' cognitive abilities. This study aims to determine the effect of the duration of playing gadgets on sleep quality in Citra Bangsa Christian Elementary School Children. This research is a quantitative research with a correlation research design and an analytical descriptive research design with a survey method approach. The number of samples in this study were 50 parents of students of Citra Bangsa Kupang Christian Elementary School with total sampling technique. Data collection techniques in this study were obtained by distributing questionnaires to respondents via google form. The data analysis technique used is the Chi-Square test. The results of this study indicate that respondents who play gadgets with high duration and have poor sleep quality are 21 people (100%). The results of the Chi-square test obtained p value = 0.000 (at <0.05) so it can be concluded that there is a significant effect between the duration of playing gadgets on sleep quality in school-aged children in grades V and VI of Citra Bangsa Christian Elementary School Kupang. The higher the duration of playing gadgets (frequency and intensity), the worse the sleep quality of students. Based on the results of the study, it is recommended for parents to increase supervision of the hours of using gadgets that can affect the quality of sleep in school-age children. Keywords: Duration Of Playing Gadgets, Sleep Quality, Elementary School